2013
DOI: 10.2355/isijinternational.53.2176
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Maximum Carbide Size in a Hypereutectic High Chromium Cast Iron Alloyed with Titanium

Abstract: In this study, in order to obtain complete size distribution results, the maximum carbide size in a Fe-17 mass% Cr-4 mass% C hypereutectic High Chromium Cast Iron (HCCI) produced with different cooling conditions, titanium additions and heat treatment conditions was determined by using the statistics of extreme values (SEV) method. In addition, the shape factor, circularity, was estimated in order to classify the type of carbides (primary M7C3 carbides, TiC carbides and secondary M7C3 carbides). Compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Fine‐tuning of NPs' size, shape, and interparticle magnetic interaction, which determine the effective magnetic field of anisotropy, are crucial to optimize the heating efficiency of a given material to be intrinsically used for magnetic hyperthermia applications. In particular, the last significant advances to increase the SAR of iron oxide NPs were mainly based on the fabrication of nanostructures with high magnetic anisotropy (e.g., magnetite cubes, rods, and octopods) and core–shell NPs that exploit the exchange and surface anisotropy appearing when soft and hard magnetic materials are join together in one single nanostructure . However, the challenge remains since high heating power in suspension solutions may not transform into efficient heating in the cellular environment, where a drastic decrease in the SAR of colloidal nanoparticle suspensions was observed when they got into endosomes as a result of the cell internalization mechanisms.…”
Section: Representative Biomedical Applicationsmentioning
confidence: 99%
“…Fine‐tuning of NPs' size, shape, and interparticle magnetic interaction, which determine the effective magnetic field of anisotropy, are crucial to optimize the heating efficiency of a given material to be intrinsically used for magnetic hyperthermia applications. In particular, the last significant advances to increase the SAR of iron oxide NPs were mainly based on the fabrication of nanostructures with high magnetic anisotropy (e.g., magnetite cubes, rods, and octopods) and core–shell NPs that exploit the exchange and surface anisotropy appearing when soft and hard magnetic materials are join together in one single nanostructure . However, the challenge remains since high heating power in suspension solutions may not transform into efficient heating in the cellular environment, where a drastic decrease in the SAR of colloidal nanoparticle suspensions was observed when they got into endosomes as a result of the cell internalization mechanisms.…”
Section: Representative Biomedical Applicationsmentioning
confidence: 99%
“…The FORCs analysis results consistent with the micromagnetics model revealed that the Janus-like structure in NCMs caused the drastic decrease in H c . In other words, the NCMs largely dominated by the core/shell-like structure provided the largest (BH) max (17.5 MGOe) in the Fe-Pd system and the highest H c /H a value (26.5%) among all NCM powders, [4][5][6][7][25][26][27][28] because of the highly sensitive change of H c induced by the extremely slight transformation of phasesegregation structures. In our previous works, 4,5 we could not correctly evaluate the decrease in H c , because it was quite difficult to discuss the boundary between 'efficient' and 'inef-cient' exchange coupling between the hard and so magnetic phases by using conventional methods such as TEM, XRD and EDS elemental mapping.…”
Section: Discussionmentioning
confidence: 98%
“…4,5,[25][26][27][28] Particularly, the H c /H a value (26.5%) was also highest among all NCM powders to our knowledge, which indicates that the performance of L1 0 -FePd/a-Fe NCMs was efficiently brought out, compared with other systems. [4][5][6][7][25][26][27] To reveal which factor contributed to the high H c /H a and (BH) max , we again conducted FORCs analysis on these NCMs (Fig. 3c).…”
Section: Correlation Of Crystal and Phase-segregation Structures Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Hard magnetic L1 0 -FePt nanoparticles prepared by the wet chemical method [15][16][17][18] have large magnetocrystalline anisotropy, small superparamagnetic critical size, controllable shape, catalytic activity, and can be aligned by a magnetic eld. 19,20 They are oen used as building blocks of exchange-coupled magnets such as FePt/Fe 3 Pt, 21,22 FePt/Co, [23][24][25] FePt/Fe, 26 FePt/ FeCo, 27,28 and FePt/Fe 3 O 4 . 15,23,29,30 Exchange-coupled FePt/Co core-shell nanoparticles with controllable Co thickness was prepared by Liu et al for the rst time, 23 where the introduction of the so phase increased the saturation magnetization (M s ) of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%